Oxygen-hybridized nonionic demulsification material as well as preparation method and application thereof

By designing oxygen hybrid non-ionic demulsification materials, using phenyl and high-density oxygen groups to enhance hydrogen bonding, the problem of poor demulsification of petroleum emulsion containing nano-solid particles in the prior art has been solved, and high efficiency has been achieved. Economical demulsification effect.

CN119143939AActive Publication Date: 2024-12-17TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411227020.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-17
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The prior art is in poor demulsification effect when treating unconventional petroleum emulsions containing nano-solid particles. Conventional demulsification agents are slow to dehydrate at high temperatures and cannot achieve complete demulsification, which is economically cost-effective.

Method used

Using oxygen hybrid non-ionic demulsification materials, the carbon chain length and branch chain are designed by building phenyl, ester group and ether bonds, and the esterification reaction is carried out with oxygen-rich organic acid and fatty alcohol non-ionic polyether to form high density The oxygen groups enhance hydrogen bonding and compatibility and improve demulsification effect.

Benefits of technology

It achieves complete demulsification in a short time (within 45 minutes) under mild conditions (below 60℃), significantly improving the demulsification efficiency and economic cost, and is suitable for unconventional oil-water emulsions with stable nano-solid particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143939A_ABST
    Figure CN119143939A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of demulsification, and provides an oxygen-hybridized nonionic demulsification material as well as a preparation method and application thereof, the preparation method of the oxygen-hybridized nonionic demulsification material comprises the following steps: (1) mixing a fatty alcohol nonionic polyether solution, a free radical initiator, olefinic acid and an oil-soluble auxiliary agent, and carrying out polymerization reaction to obtain a first polymer; and (2) carrying out catalytic esterification reaction on oxygen-enriched organic acid and the first polymer to obtain an esterification reaction system, and removing the solvent from the esterification reaction system to obtain the oxygen-hybridized nonionic demulsification material. The oxygen-enriched organic acid and the oil-soluble additive are used as modified substances, so that the ability of the oxygen-hybridized nonionic demulsification material to destroy an oil-water interfacial film and the solubility of the oxygen-hybridized nonionic demulsification material in an oil phase are remarkably improved, the demulsification effect on unconventional petroleum emulsion with stable nano-micro solid particles is excellent, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of demulsification, and in particular to an oxygen-hybridized nonionic demulsification material and a preparation method and application thereof. Background Art

[0002] With the continuous development of industrial technology, the world's oil demand is increasing year by year. However, with the increasing depletion of conventional oil resources, the exploitation of some important oil supplementary resources, such as oil sands, shale oil, tight oil, and extra heavy oil, has gradually entered the production process of the oil industry.

[0003] In the process of unconventional oil production, a key problem to be solved is to carry out the demulsification of oil-water emulsion, because there is wherein the natural interfacial active substance that can stabilize the oil-water emulsion, such as asphaltenes, colloids, cyclohexane acid etc., these as natural emulsifiers, can form an interfacial film with certain mechanical strength, and this interfacial film can be strongly adsorbed on the surface of water molecules so that the oil-water two-phase exists in the form of stable emulsified state. In addition, the nano-micro solid particles inevitably introduced in the production process, such as silicon dioxide, calcium carbonate, clay etc., can act together with the above natural emulsifier molecules, can significantly enhance the mechanical strength of the oil-water interfacial film and the stability of the emulsion, and greatly increase the difficulty of demulsification. The oil-water emulsions formed by these not only bring great difficulties (corrosion equipment, catalyst poisoning, increase transportation cost) to subsequent processing, but also have a strong impact on the quality of oil products, therefore the demulsification dehydration of oil-water emulsion must be carried out to improve the quality of oil, to reach the requirement of subsequent oil refining processing stage.

[0004] At present, conventional demulsifiers are mostly used to treat unconventional petroleum emulsions, such as SP169 (polyoxypropylene polyoxyethylene octadecyl alcohol ether block copolymer), AE1951 (polyethylene polyamine polyoxyethylene polyoxypropylene ether), AP2050 (fatty alcohol non-ionic polyether demulsifier), etc. Conventional demulsifiers have good demulsification effect on the interfacial film formed by asphaltene, colloid and other interfacial active components in crude oil as the main substances, but the structure of the interfacial film formed by the interaction between nano-solid particles in unconventional petroleum emulsions and the natural emulsifiers therein is very stable, and the applicability of conventional demulsifiers is poor, which is mainly reflected in the high demulsification temperature (above 80°C) and slow dehydration speed.

[0005] Chinese patent CN116023667A discloses a demulsifier containing a large number of tertiary amine groups. The synthesis process mainly includes first mixing N,N-dimethyl-1,3-propylenediamine, maleic anhydride and an organic solvent for acylation reaction to obtain a first intermediate, then mixing the first intermediate with acrylic acid and a free radical initiator for copolymerization to obtain a second intermediate, and then mixing the second intermediate with phenolic resin polyether for esterification reaction to obtain a demulsifier. However, the demulsifier has a long demulsification time for crude oil emulsion (>120 minutes) and cannot achieve complete dehydration. The demulsification rate is only between 85.7% and 97.1%, and the dehydration effect on emulsions containing nano-micro solid particles is unclear.

[0006] Chinese patent CN112915592A discloses a magnetic nano-emulsifier for oil-water emulsion demulsification, which is mainly obtained by reacting ferroferric oxide particles, organic solvents, water, silicon sources, silane coupling agents, hydroxyl-terminated polyethers, etc., and performing solid-liquid separation, washing and drying. The organic groups and magnetic particles in the demulsifier can work synergistically to shorten the demulsification time, but the demulsifier cannot achieve complete demulsification (90%) of the oil-water emulsion, and the dosage is large (>3000mg / L), and the economic cost is high.

[0007] In summary, it can be seen that it is still difficult to achieve complete demulsification of unconventional petroleum emulsions containing particles, and it is urgent to develop new demulsifiers or processes to optimize the demulsification effect. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides an oxygen-hybridized nonionic demulsifying material and a preparation method and application thereof. By constructing a phenyl group, an ester group and an ether bond, and combining and designing the length and branching of the carbon chain, a structure shown in formula (1) is obtained, wherein the oxygen atom can help the demulsifier to form more hydrogen bonds with the emulsified water droplets, and the phenyl group can improve the similar compatibility with asphaltene, thereby ultimately improving the demulsification effect.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides an oxygen-hybridized nonionic demulsifier material, wherein the oxygen-hybridized nonionic demulsifier material comprises a structure as described in formula (1):

[0011]

[0012] In formula (1), the value range of x is 40-60, the value range of y is 30-50, the value range of n is 10-20, the value range of x' is 20-30, and the value range of y' is 1-10.

[0013] Through various research and design, the present invention finds that the oxygen-hybridized nonionic demulsifying material having the structure of formula (1) has excellent demulsifying effect on unconventional oil-water emulsions stabilized by micro-nano solid particles, wherein the phenyl group has a better miscibility with the condensed rings in asphaltene, and the high density of oxygen groups can enhance the multi-hydrogen bonding effect, thereby strengthening the interaction with asphaltene at the oil-water interface. In addition, the high content of oxygen groups has a stronger ability to reconstruct non-covalent bonds, which is more conducive to demulsification.

[0014] Furthermore, the present invention controls the value range of x to be 50-60. When the chain segments of x are too many, the hydrophilicity of the demulsifier molecule is too strong, and there is a problem of poor solubility in the oil phase. When the chain segments of x are too few, the hydrogen bonding ability of the demulsifier molecule and the water molecule is insufficient, and there is a problem of reduced demulsification ability; the value range of y is 30-40. When the chain segments of y are too many, the lipophilicity of the demulsifier molecule is too strong, and the hydrogen bonding ability with the water molecule is insufficient, and there is a problem of reduced demulsification ability. When the chain segments of y are too few, the lipophilicity of the demulsifier molecule is insufficient, and there is a problem of poor solubility in the oil phase; the value range of n is 10-20. When the chain segments of n are too many, the hydrophilicity of the demulsifier molecule is too strong. The water property is too strong, and there is a problem of poor solubility in the oil phase. When the chain segments of n are too few, the hydrogen bonding ability of the demulsifier molecules and the water molecules is insufficient, and there is a problem of decreased demulsification ability; the value range of x' is 20-30. When the chain segments of x' are too many, the hydrophilicity of the demulsifier molecules is too strong, and there is a problem of poor solubility in the oil phase. When the chain segments of x' are too few, the hydrogen bonding ability of the demulsifier molecules and the water molecules is insufficient, and there is a problem of decreased demulsification ability; the value range of y' is 1-10. When the chain segments of y' are too many, the lipophilicity of the demulsifier molecules is too strong, and there is a problem of decreased water solubility. When the chain segments of y' are too few, the miscibility of the demulsifier molecules and the asphaltene condensed rings is insufficient.

[0015] wherein the value range of x is 50-60, for example, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 or 60; the value range of y is 30-40, for example, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 or 40; the value range of n is 10-20, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20; the value range of x' is 20-30, for example, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30; the value range of y' is 1-10, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0016] Therefore, the present invention selects the above-mentioned number of segments to achieve a better demulsification effect.

[0017] Preferably, the oxygen content in the oxygen-hybridized nonionic demulsifier is 30wt% to 40wt%, for example, it can be 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% or 40wt%, etc.

[0018] The present invention has no special restrictions on the preparation method of the oxygen-hybridized nonionic demulsifying material provided in the first aspect, and can be prepared by methods well known to those skilled in the art, preferably by the preparation method provided by the second aspect of the present invention, which has the advantages of simple process and better demulsification effect.

[0019] In a second aspect, the present invention provides a method for preparing the oxygen-hybridized nonionic demulsifier material, the preparation method comprising the following steps:

[0020] (1) mixing a solution of a fatty alcohol nonionic polyether, a free radical initiator, an olefinic acid and an oil-soluble additive to carry out a polymerization reaction to obtain a first polymer;

[0021] (2) The oxygen-rich organic acid and the first polymer are subjected to a catalytic esterification reaction to obtain an esterification reaction system. After the solvent is removed from the esterification reaction system, the oxygen-hybridized nonionic demulsifying material is obtained.

[0022] The preparation method provided in the second aspect of the present invention first selects oxygen-rich organic acid and oil-soluble auxiliary agent as modifying substances, which can significantly improve the ability of the demulsifier to destroy the oil-water interface film and the solubility of the demulsifier in the oil phase; and the oxygen-rich organic acid can help the demulsifier to form more hydrogen bonds with the emulsified water droplets through its own oxygen atoms, thereby promoting demulsification, and the benzene ring and long alkyl chain in the oil-soluble auxiliary agent can promote the compatibility between the demulsifier and the oil phase; further, the oxygen-rich organic acid can undergo esterification and dehydration reaction with fatty alcohol non-ionic polyether to generate more oxygen-rich groups, which is beneficial to improving the demulsification ability of the demulsifier.

[0023] Preferably, the solvent in the solution of the fatty alcohol nonionic polyether in step (1) is an organic solvent.

[0024] Preferably, the organic solvent comprises an aromatic hydrocarbon organic solvent.

[0025] Preferably, the aromatic organic solvent comprises any one of toluene, xylene, trimethylbenzene or ethylbenzene, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of toluene and xylene, a combination of toluene and trimethylbenzene, a combination of trimethylbenzene and xylene, and a combination of ethylbenzene and xylene.

[0026] Preferably, the fatty alcohol nonionic polyether is a linear type, and preferably, the fatty alcohol nonionic polyether is formed by polymerization of ethylene oxide and propylene oxide with propylene glycol as an initiator.

[0027] Preferably, the molar ratio of ethylene oxide to propylene oxide is 1 to 2:1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc.

[0028] Preferably, the molecular weight of the fatty alcohol nonionic polyether is 3000-5000, for example, 3000, 3200, 3300, 3400, 3500, 3600, 3700, 3800, 4000, 4200, 4500, 4800 or 5000.

[0029] Preferably, the molar ratio of the sum of propylene glycol, ethylene oxide and propylene oxide is 1 to 2:1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc.

[0030] Preferably, the ratio of the fatty alcohol nonionic polyether single agent to the organic solvent is 1 to 60 g:100 mL, for example, it can be 1 g:100 mL, 8 g:100 mL, 15 g:100 mL, 21 g:100 mL, 28 g:100 mL, 34 g:100 mL, 41 g:100 mL, 47 g:100 mL, 54 g:100 mL or 60 g:100 mL, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0031] Preferably, the free radical initiator comprises any one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide or dicumyl peroxide, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of azobisisobutyronitrile and azobisisoheptanenitrile, a combination of benzoyl peroxide and azobisisoheptanenitrile, a combination of azobisisobutyronitrile and benzoyl peroxide, and a combination of dicumyl peroxide and azobisisoheptanenitrile.

[0032] Preferably, the free radical initiator accounts for 0.01 to 1 wt% of the mass of the fatty alcohol nonionic polyether, for example, it can be 0.01 wt%, 0.12 wt%, 0.23 wt%, 0.34 wt%, 0.45 wt%, 0.56 wt%, 0.67 wt%, 0.78 wt%, 0.89 wt% or 1 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0033] Preferably, the olefinic acid comprises an olefinic acid containing at least one carboxyl group and having 3 to 20 carbon atoms, and the carbon atoms may be, for example, 3, 5, 7, 9, 11, 13, 15, 17, 19 or 20, but is not limited to the listed values, and other values ​​not listed in the range are also applicable. Preferably, it comprises any one or a combination of at least two of 2-butenoic acid, oleic acid, acrylic acid or undecylenic acid, wherein a typical but non-limiting combination is a combination of 2-butenoic acid and oleic acid, a combination of acrylic acid and oleic acid, a combination of 2-butenoic acid and acrylic acid, and a combination of undecylenic acid and oleic acid.

[0034] Preferably, the olefinic acid accounts for 1 to 30 wt% of the mass of the fatty alcohol nonionic polyether, for example, it can be 1 wt%, 5 wt%, 8 wt%, 11 wt%, 14 wt%, 18 wt%, 21 wt%, 24 wt%, 27 wt% or 30 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0035] The present invention further preferably controls the content of olefinic acid within the above range, which can better improve the solubility of the demulsifying material in the oil phase and provide more hydrogen bonding sites to achieve more excellent demulsifying performance.

[0036] Preferably, the oil-soluble auxiliary agent includes any one of vinyltoluene, styrene propylene or styrene, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of vinyltoluene and styrene propylene, a combination of styrene and styrene propylene, and a combination of vinyltoluene and styrene.

[0037] Preferably, the oil-soluble auxiliary agent accounts for 0.1 to 10 wt% of the mass of the fatty alcohol nonionic polyether, for example, it can be 0.1 wt%, 1.2 wt%, 2.3 wt%, 3.4 wt%, 4.5 wt%, 5.6 wt%, 6.7 wt%, 7.8 wt%, 8.9 wt% or 10 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0038] The present invention further preferably controls the mass ratio of the oil-soluble additive to the fatty alcohol nonionic polyether within the above range, which can take into account the solubility of the demulsifying material in the oil phase and the water phase, thereby ultimately improving the demulsification performance.

[0039] Preferably, the polymerization reaction temperature is 60-100°C, for example, 60°C, 65°C, 69°C, 74°C, 78°C, 83°C, 87°C, 92°C, 96°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0040] Preferably, the polymerization reaction duration is 2 to 8 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 6 hours, 7 or 8 hours.

[0041] Preferably, the oxygen-rich organic acid in step (2) comprises any one of lactic acid, citric acid or linoleic acid, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of lactic acid and citric acid, a combination of linoleic acid and citric acid, and a combination of lactic acid and linoleic acid.

[0042] The present invention further prefers that the oxygen-enriched organic acid is lactic acid, citric acid or linoleic acid. Compared with other organic acids, these acids can not only better form hydrogen bonding sites during the demulsification process, but also are well compatible with the oil phase and have a better demulsification effect.

[0043] Preferably, the oxygen-rich organic acid accounts for 0.1 to 10 wt% of the mass of the fatty alcohol nonionic polyether, for example, it can be 0.1 wt%, 1.2 wt%, 2.3 wt%, 3.4 wt%, 4.5 wt%, 5.6 wt%, 6.7 wt%, 7.8 wt%, 8.9 wt% or 10 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0044] The present invention further preferably controls the content of the oxygen-rich organic acid within the above range, which can better take into account the formation of hydrogen bonding sites of the demulsifying material or the solubility of the demulsifying material in the oil phase, and ultimately improve the demulsifying effect of the demulsifying material, and has broad application prospects.

[0045] Preferably, the temperature of the catalytic esterification reaction is 80-150°C, for example, it can be 80°C, 88°C, 96°C, 104°C, 112°C, 119°C, 127°C, 135°C, 143°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0046] Preferably, the duration of the catalytic esterification reaction is 2 to 8 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 6 hours, 7 or 8 hours.

[0047] Preferably, the catalyst for catalyzing the esterification reaction is an organic catalyst.

[0048] Preferably, the organic catalyst comprises sulfonic acid and / or an organic acid salt.

[0049] Preferably, the sulfonic acid comprises an aryl sulfonic acid, preferably any one of benzenesulfonic acid, p-toluenesulfonic acid, o-toluenesulfonic acid or m-toluenesulfonic acid or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of benzenesulfonic acid and p-toluenesulfonic acid, a combination of o-toluenesulfonic acid and p-toluenesulfonic acid, a combination of benzenesulfonic acid and o-toluenesulfonic acid, and a combination of m-toluenesulfonic acid and o-toluenesulfonic acid.

[0050] Preferably, the organic acid salt comprises an acetate, preferably any one or a combination of at least two of zinc acetate, cobalt acetate or ferric acetate, wherein a typical but non-limiting combination is a combination of zinc acetate and cobalt acetate, and a combination of ferric acetate and cobalt acetate.

[0051] Preferably, the organic catalyst accounts for 0.01 to 1 wt% of the mass of the fatty alcohol nonionic polyether, for example, it can be 0.01 wt%, 0.12 wt%, 0.23 wt%, 0.34 wt%, 0.45 wt%, 0.56 wt%, 0.67 wt%, 0.78 wt%, 0.89 wt% or 1 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0052] Preferably, said removing the solvent comprises drying.

[0053] Preferably, the drying temperature is 80-150°C, for example, it can be 80°C, 88°C, 96°C, 104°C, 112°C, 119°C, 127°C, 135°C, 143°C or 150°C, but is not limited to the listed values, and other values ​​not listed in this range are equally applicable. The pressure is -0.1MPa to -0.5MPa, for example, it can be -0.1MPa, -0.15MPa, -0.2MPa, -0.25MPa, -0.3MPa, -0.35MPa, -0.4MPa, -0.45MPa or -0.5MPa, and the time is 20-120min, for example, it can be 20min, 32min, 43min, 54min, 65min, 76min, 87min, 98min, 109min or 120min, but is not limited to the listed values, and other values ​​not listed in this range are equally applicable.

[0054] In a third aspect, the present invention provides an application of the oxygen-hybrid nonionic demulsifier material described in the first aspect or the oxygen-hybrid nonionic demulsifier material prepared by the preparation method of the oxygen-hybrid nonionic demulsifier material described in the second aspect, wherein the oxygen-hybrid nonionic demulsifier material is used for demulsifying unconventional oil-water emulsions containing nano-micro solid particles.

[0055] The oxygen-hybridized nonionic demulsifying material provided by the present invention has an excellent demulsifying effect on unconventional oil-water emulsions containing nano-micro solid particles, thereby making up for the problem of insufficient demulsifying performance of such oil-water emulsions in the existing market.

[0056] Preferably, the particle size of the nanomicro solid particles in the unconventional oil-water emulsion containing nanomicro solid particles is 20nm to 10μm, for example, it can be 20nm, 21nm, 25nm, 100nm, 200nm, 300nm, 400nm, 500nm, 1μm, 2μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm, etc.

[0057] The nano-micro solid particles of the present invention have a small particle size and therefore have extremely high stability at the oil-water interface, which increases the difficulty of oil-water demulsification.

[0058] Preferably, the unconventional oil-water emulsion containing nano-micro solid particles is a water-in-oil emulsion.

[0059] Preferably, the viscosity of the unconventional oil-water emulsion containing nano-micro solid particles is 50 to 500 mPa·s, for example, it can be 50 mPa·s, 100 mPa·s, 150 mPa·s, 200 mPa·s, 250 mPa·s, 300 mPa·s, 350 mPa·s, 400 mPa·s, 450 mPa·s or 500 mPa·s, etc.

[0060] Preferably, the asphaltene content in the unconventional oil-water emulsion containing nano-micro solid particles is 0.1-5wt%, for example, it can be 0.1wt%, 0.7wt%, 1.2wt%, 1.8wt%, 2.3wt%, 2.9wt%, 3.4wt%, 4wt%, 4.5wt% or 5wt%, etc.

[0061] Preferably, the water content in the unconventional oil-water emulsion containing nano-micro solid particles is 10-75wt%, for example, it can be 10wt%, 18wt%, 25wt%, 32wt%, 39wt%, 47wt%, 54wt%, 61wt%, 68wt% or 75wt%, etc.

[0062] Preferably, the content of nano-solid particles in the unconventional oil-water emulsion containing nano-solid particles is 0.1-2wt%, for example, it can be 0.1wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, etc.

[0063] Preferably, the demulsification time is 30 min to 120 min, for example, it can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.

[0064] Preferably, the demulsification temperature is 40°C to 60°C, for example, it can be 40°C, 43°C, 45°C, 47°C, 49°C, 52°C, 54°C, 56°C, 58°C or 60°C.

[0065] Preferably, the amount of oxygen-hybridized nonionic demulsifying material added in the demulsifier is 100 mg / L to 1200 mg / L, for example, it can be 100 mg / L, 220 mg / L, 345 mg / L, 460 mg / L, 580 mg / L, 710 mg / L, 830 mg / L, 950 mg / L, 1070 mg / L or 1200 mg / L, etc.

[0066] Compared with the prior art, the present invention has at least the following beneficial effects:

[0067] (1) The oxygen-hybridized nonionic demulsifier provided by the present invention can help the demulsifier to form more hydrogen bonds with the emulsified water droplets through its own oxygen atoms, thereby promoting demulsification, and the benzene ring and the long alkyl chain can promote the compatibility between the demulsifier and the oil phase. The two synergistically enhance the destructive effect on the oil-water interface, and ultimately have an excellent demulsification effect;

[0068] (2) The oxygen-hybridized nonionic demulsifier provided by the present invention generates more oxygen-rich groups by esterification and dehydration reaction between oxygen-rich organic acid and fatty alcohol nonionic polyether. The high-density oxygen groups can not only provide more hydrogen bonds, but also have stronger non-covalent bond reconstruction ability, which is beneficial to improve the demulsification ability of the oxygen-hybridized nonionic demulsifier;

[0069] (3) The oxygen-hybridized nonionic demulsifying material provided by the present invention is used in unconventional oil-water emulsions stabilized by micro-nano particles. The demulsification time is as short as 45 minutes, the conditions are mild, generally within 60°C, and 100% complete demulsification can be achieved. The demulsification effect is excellent and the application prospect is broad. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 This is the nuclear magnetic hydrogen spectrum of the oxygen-hybridized nonionic demulsifier material prepared in Example 1 of the present invention.

[0071] Figure 2 This is the infrared spectrum of the oxygen-hybridized nonionic demulsifier material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0072] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0073] Example 1

[0074] This embodiment provides an oxygen-hybridized nonionic demulsifier material, and the preparation method of the oxygen-hybridized nonionic demulsifier material comprises the following steps:

[0075] (1) At room temperature, 10 g of fatty alcohol nonionic polyether (brand number 2040, molecular weight 4000) is added to a container equipped with a thermometer, a stirring component, and a reflux condensing component. The fatty alcohol nonionic polyether is formed by polymerization of ethylene oxide and propylene oxide in a ratio of 2:1 with propylene glycol as an initiator, and then 100 mL of xylene is added to completely dissolve the fatty alcohol nonionic polyether under stirring at 150 r / min; then 2 g of acrylic acid, 1 g of styrene, and 0.02 g of benzoyl peroxide are added, and the temperature is gradually raised to 80° C., and a polymerization reaction is carried out for 2 hours to obtain a first polymer;

[0076] (2) Add 1 g of lactic acid and 0.04 g of p-toluenesulfonic acid to the first polymer, raise the system temperature to 130° C., and carry out a catalytic esterification reaction for 4 hours to obtain an esterification reaction system; then evaporate the xylene solvent in the esterification reaction system, and dry the obtained liquid in a vacuum drying oven at 80° C. for 60 minutes to obtain an oxygen-hybridized nonionic demulsifier.

[0077] The equations in the preparation process of this embodiment are shown in the following equations (2) to (4):

[0078]

[0079] The oxygen-hybridized nonionic demulsifier prepared in this embodiment includes the structure described in formula (1):

[0080]

[0081] In formula (1), the value of x is 55, the value of y is 35, the value of n is 15, the value of x' is 25, and the value of y' is 8.

[0082] The nuclear magnetic hydrogen spectrum and infrared spectrum of the oxygen hybrid nonionic demulsifier material prepared in this example are shown as follows: Figure 1 and Figure 2 As shown, from Figure 1 and Figure 2It can be seen that the oxygen-hybridized nonionic demulsifier prepared in this embodiment has a carboxyl group. The absorption peak at 12.3 ppm in the NMR spectrum indicates that a carboxyl group is introduced into the demulsifier, and the absorption peak at 7.1 ppm indicates that a phenyl group is introduced into the demulsifier. The ester peak (1736 cm -1 ) and ether peak (1109cm -1 ), which indicates that the oxygen-hybridized nonionic demulsifier in formula (1) was successfully synthesized.

[0083] Example 2

[0084] The present embodiment provides an oxygen-hybridized nonionic demulsifier. The preparation method of the oxygen-hybridized nonionic demulsifier is the same as that of Example 1, except that 8 g of fatty alcohol nonionic polyether is added, 0.04 g of benzoyl peroxide is added, 0.06 g of p-toluenesulfonic acid is added, the polymerization reaction time is 3 hours, and the esterification dehydration reaction time is 3 hours. The preparation method is not repeated here.

[0085] Example 3

[0086] The present embodiment provides an oxygen-hybridized nonionic demulsifier. The preparation method of the oxygen-hybridized nonionic demulsifier is the same as that of Example 1, except that 6 g of fatty alcohol nonionic polyether is added, 0.06 g of benzoyl peroxide is added, 0.04 g of p-toluenesulfonic acid is added, the polymerization reaction time is 4 hours, and the esterification dehydration reaction time is 5 hours. The details are not repeated here.

[0087] Example 4

[0088] The present embodiment provides an oxygen-hybridized nonionic demulsifier material. The preparation method of the oxygen-hybridized nonionic demulsifier material is the same as that of Example 1, except that 12 g of fatty alcohol nonionic polyether is added, 0.1 g of benzoyl peroxide is added, 0.1 g of p-toluenesulfonic acid is added, the polymerization reaction time is 6 hours, and the esterification dehydration reaction time is 6 hours. The details are not repeated here.

[0089] Example 5

[0090] This embodiment provides an oxygen-hybridized nonionic demulsifier. The preparation method of the oxygen-hybridized nonionic demulsifier is the same as that of Example 1, except that 20 g of fatty alcohol nonionic polyether, 5 g of acrylic acid and 2 g of lactic acid are added, and will not be repeated here.

[0091] Example 6

[0092] The present embodiment provides an oxygen-hybridized nonionic demulsifier. The preparation method of the oxygen-hybridized nonionic demulsifier is the same as that of Example 1, except that the olefin acid is a mixture of acrylic acid and 2-butenoic acid, each with a mass of 1 g, the solvent is a mixed solvent of xylene and toluene, each with 50 mL, the free radical modifier is a mixture of azobisisobutyronitrile and benzoyl peroxide, each with 0.01 g added, the polymerization reaction temperature is 90° C., and the esterification dehydration reaction temperature is 120° C., and the rest is not repeated here.

[0093] Example 7

[0094] The present embodiment provides an oxygen-hybridized nonionic demulsifying material. The preparation method of the oxygen-hybridized nonionic demulsifying material is the same as that of Example 1, except that the olefin acid is a mixture of oleic acid, acrylic acid, and 2-butenoic acid, each with a mass of 1.0 g, the oil-soluble additive is a mixture of styrene, propylene, and styrene, each with a mass of 0.5 g, the solvent is a mixed solvent of xylene and trimethylolbenzene, each with 50 mL, and the organic acid catalyst is a mixture of benzenesulfonic acid, p-toluenesulfonic acid, and m-toluenesulfonic acid, each of which is added with 0.02 g. The details are not repeated here.

[0095] Example 8

[0096] The present embodiment provides an oxygen-hybridized nonionic demulsifying material. The preparation method of the oxygen-hybridized nonionic demulsifying material is the same as that of Example 1, except that the olefin acid is a mixture of oleic acid and acrylic acid, each with a mass of 1.0 g, the solvent is a mixed solvent of xylene, trimethylbenzene and toluene, each with a mass of 30 mL, the oil-soluble auxiliary agent is a mixture of vinyltoluene and styrene, each with a mass of 0.5 g, the organic acid catalyst is a mixture of benzenesulfonic acid, p-toluenesulfonic acid and m-toluenesulfonic acid, each of which is added with 0.02 g, and the free radical modifier is a mixture of azobisisobutyronitrile and benzoyl peroxide, each of which is added with 0.01 g. The rest is not repeated here.

[0097] Example 9

[0098] The present embodiment provides an oxygen-hybridized nonionic demulsifying material. The preparation method of the oxygen-hybridized nonionic demulsifying material is the same as that of Example 1, except that the olefin acid is a mixture of undecylenic acid, acrylic acid and oleic acid, each with a mass of 0.5 g, the solvent is a mixed solvent of trimethylolbenzene and toluene, each with a mass of 50 mL, the oil-soluble auxiliary agent is a mixture of vinyltoluene and styrene, each with a mass of 0.5 g, the organic acid catalyst is a mixture of benzenesulfonic acid, p-toluenesulfonic acid and m-toluenesulfonic acid, each of which is added with 0.03 g, and the free radical modifier is a mixture of azobisisobutyronitrile and azobisisoheptylonitrile, each of which is added with 0.02 g. The rest is not repeated here.

[0099] Example 10

[0100] The present embodiment provides an oxygen-hybridized nonionic demulsifying material. The preparation method of the oxygen-hybridized nonionic demulsifying material is the same as that of Example 1, except that the olefin acid is a mixture of oleic acid and undecylenic acid, each with a mass of 0.8 g, the solvent is a mixed solvent of xylene, trimethylolbenzene and toluene, each with a mass of 30 mL, the oil-soluble auxiliary agent is a mixture of vinyltoluene, styrene and styrene propene, each with a mass of 0.3 g, the organic acid catalyst is a mixture of p-toluenesulfonic acid and m-toluenesulfonic acid, each with a mass of 0.03 g, and the free radical modifier is a mixture of azobisisobutyronitrile and diisopropylbenzene peroxide, each with a mass of 0.02 g. The details are not repeated here.

[0101] Embodiment 11

[0102] This embodiment provides an oxygen-hybridized nonionic demulsifier. The oxygen-hybridized nonionic demulsifier is the same as that of Embodiment 1 except that 4 g of acrylic acid is added, and details thereof will not be repeated herein.

[0103] Example 12

[0104] This embodiment provides an oxygen-hybridized nonionic demulsifier. The oxygen-hybridized nonionic demulsifier is the same as that of Embodiment 1 except that 0.05 g of acrylic acid is added, and details thereof will not be repeated herein.

[0105] Embodiment 13

[0106] This embodiment provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as that of Embodiment 1 except that 0.005 g of styrene is added, and details thereof will not be repeated herein.

[0107] Embodiment 14

[0108] This embodiment provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as that of Embodiment 1 except that 1.5 g of styrene is added, and details thereof will not be repeated herein.

[0109] Embodiment 15

[0110] This embodiment provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as that of Embodiment 1 except that lactic acid is replaced by formic acid, and will not be described in detail herein.

[0111] Example 16

[0112] This embodiment provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as that of Embodiment 1 except that 1.2 g of lactic acid is added, and details thereof will not be repeated herein.

[0113] Embodiment 17

[0114] This embodiment provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as that of Embodiment 1 except that 0.005 g of lactic acid is added, and details thereof will not be repeated herein.

[0115] Embodiment 18

[0116] This embodiment provides an oxygen-hybridized nonionic demulsifier material, and the preparation method of the oxygen-hybridized nonionic demulsifier material comprises the following steps:

[0117] (1) At 40° C., 10 g of fatty alcohol nonionic polyether (brand number 2040, molecular weight 5000, Nantong Derui Chemical Co., Ltd.) was added to a container equipped with a thermometer, a stirring component, and a reflux condensing component. The fatty alcohol nonionic polyether was formed by polymerization of ethylene oxide and propylene oxide in a ratio of 2:1 with propylene glycol as an initiator, and then 110 mL of xylene was added. The fatty alcohol nonionic polyether was completely dissolved under stirring at 150 r / min. Then, 2.3 g of acrylic acid, 0.8 g of styrene, and 0.02 g of benzoyl peroxide were added, and the temperature was gradually raised to 60° C., and a polymerization reaction was carried out for 4 hours to obtain a first polymer;

[0118] (2) Add 0.8 g of lactic acid and 0.03 g of p-toluenesulfonic acid to the first polymer, raise the system temperature to 150° C., and carry out a catalytic esterification reaction for 2 hours to obtain an esterification reaction system; then evaporate the xylene solvent in the esterification reaction system, and dry the obtained liquid in a vacuum drying oven at 75° C. for 80 minutes to obtain an oxygen-hybridized nonionic demulsifier.

[0119] Comparative Example 1

[0120] This comparative example provides a demulsifier, which is a commercially available demulsifier AP2040 (Nantong Derui Chemical Co., Ltd.).

[0121] Comparative Example 2

[0122] This comparative example provides a demulsifier, which is a commercially available demulsifier BP2050 (Nantong Derui Chemical Co., Ltd.).

[0123] Comparative Example 3

[0124] This comparative example provides a demulsifier, which is a commercially available demulsifier AE1951 (Nantong Derui Chemical Co., Ltd.).

[0125] Comparative Example 4

[0126] This comparative example provides a demulsifier, which is a commercially available demulsifier SP169 (Nantong Derui Chemical Co., Ltd.).

[0127] Comparative Example 5

[0128] This comparative example provides a demulsifier, which is the commercially available demulsifier OWT101 (Guangzhou Xiaozhong Environmental Protection Technology Co., Ltd.).

[0129] Comparative Example 6

[0130] This comparative example provides a demulsifier, which is the commercially available demulsifier OWT102 (Guangzhou Xiaozhong Environmental Protection Technology Co., Ltd.).

[0131] Comparative Example 7

[0132] This comparative example provides a demulsifier, which is the commercially available demulsifier OWT103 (Guangzhou Xiaozhong Environmental Protection Technology Co., Ltd.).

[0133] Comparative Example 8

[0134] This comparative example provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as Example 1 except that acrylic acid is replaced by acetic acid, and the details are not described again.

[0135] Comparative Example 9

[0136] This comparative example provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as Example 1 except that styrene is replaced by ethylene, and the details are not described again.

[0137] Comparative Example 10

[0138] This comparative example provides an oxygen-hybridized nonionic demulsifier material. The oxygen-hybridized nonionic demulsifier material is the same as Example 1 except that lactic acid is not added, and will not be described in detail here.

[0139] Application Example 1

[0140] This application example provides an application of an oxygen-hybridized non-ionic demulsifier material, and the application is carried out using the oxygen-hybridized non-ionic demulsifier material provided in Example 1. The specific steps include: a demulsification experiment of an unconventional petroleum emulsion stabilized by nano-micro solid particles (hereinafter referred to as "emulsion", with a viscosity of 150 mPa·s, an asphaltene content of 1 wt%, a water content of 30%, a nano-micro solid particle content of 1.5 wt%, and a particle size D50 of 2 μm of the nano-micro solid particles): the demulsifier prepared by Example 1 is added to an emulsion with a water content of 30% (volume fraction), the emulsion is pre-placed in a stoppered measuring cylinder with a scale, the amount of demulsifier added is 800 ppm, and then the stoppered measuring cylinder is placed in a water bath at 60°C for demulsification to obtain separated oil phase and water phase.

[0141] Application Examples 2 to 17 and Comparative Application Examples 1 to 10

[0142] Application Examples 2 to 17 and Comparative Examples 1 to 10 provide an application of an oxygen-hybridized nonionic demulsifier. Except that the oxygen-hybridized nonionic demulsifiers in Examples 2 to 17 and Comparative Examples 1 to 10 are used respectively, and the amount of oxygen-hybridized nonionic demulsifier added in Application Example 4, Application Example 6, and Application Example 8 is 1000 ppm, and the amount of oxygen-hybridized nonionic demulsifier added in Application Example 10 is 1200 ppm, the rest are the same as Application Example 1 and will not be repeated here.

[0143] Application Example 18

[0144] This application example provides an application of an oxygen-hybridized non-ionic demulsifier material, and the application is carried out using the oxygen-hybridized non-ionic demulsifier provided in Example 18, and the specific steps include: a demulsification experiment of an unconventional petroleum emulsion stabilized by nano-micro solid particles (hereinafter referred to as "emulsion", with a viscosity of 500 mPa·s, an asphaltene content of 2 wt%, a water content of 50%, a nano-micro solid particle content of 2 wt%, and a particle size D50 of 500 nm): the demulsifier prepared by Example 1 is added to an emulsion with a water content of 50% (volume fraction), the emulsion is pre-placed in a stoppered measuring cylinder with a scale, the amount of demulsifier added is 850 ppm, and then the stoppered measuring cylinder is placed in a water bath at 50°C for demulsification to obtain separated oil phase and water phase.

[0145] The application of the oxygen-hybridized nonionic demulsifying materials provided in Application Examples 1 to 10 and Application Example 18 can achieve a demulsification efficiency of 100% within 45 minutes, and has broad application prospects.

[0146] Compared with Application Examples 11-12, Application Example 1 has more or less acrylic acid in Application Examples 11-12, which results in decreased solubility of the demulsifier in the oil phase or insufficient hydrogen bonding sites, resulting in decreased demulsification performance.

[0147] Compared with Application Examples 13-14, Application Example 1 has more or less acrylic acid in Application Examples 13-14, which results in decreased solubility of the demulsifier in the oil phase or decreased water solubility of the demulsifier, resulting in decreased demulsification performance.

[0148] Compared with Application Examples 15 to 17, Application Example 1 uses formic acid, and the hydrogen bonding sites formed by the demulsifier are insufficient, resulting in a decrease in demulsification performance; when more lactic acid is used in Application Examples 16 to 17, the solubility of the demulsifier in the oil phase is reduced, and when less lactic acid is used, the hydrogen bonding sites formed by the demulsifier are insufficient, ultimately resulting in a decrease in demulsification performance.

[0149] When commercially available demulsifiers are used in Comparative Examples 1 to 10 or a certain raw material of the demulsifier in the present invention is removed, the demulsification performance is significantly reduced compared with that in Application Example 1.

[0150] The demulsification efficiency in the present invention is calculated by dividing the volume of separated water by the total volume of water in the emulsion. The test results of the above application examples and comparative application examples are shown in Table 1.

[0151] Table 1

[0152]

[0153]

[0154] In summary, it can be seen that the new oxygen-hybridized nonionic demulsifier material provided by the present invention has excellent demulsification performance. The demulsifier prepared by combining oxygen-rich organic acid with oil-soluble additives and fatty alcohol nonionic polyether has better demulsification performance for unconventional petroleum emulsions stabilized by nanoparticles than the single polyether demulsifier. The effect of strengthening demulsification during the demulsification process is significant, and 100% demulsification efficiency can be achieved within 45 minutes.

[0155] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An oxygen hybrid nonionic demulsifier material, It is characterized in that The oxygen-hybridized nonionic demulsifying material comprises the structure of formula (1): In formula (1), the value range of x is 40-60, the value range of y is 30-50, the value range of n is 10-20, the value range of x' is 20-30, and the value range of y' is 1-10.

2. A method for preparing the oxygen-hybridized nonionic demulsifier material according to claim 1, It is characterized in that The preparation method comprises the following steps: (1) mixing a solution of a fatty alcohol nonionic polyether, a free radical initiator, an olefinic acid and an oil-soluble additive to carry out a polymerization reaction to obtain a first polymer; (2) The oxygen-rich organic acid and the first polymer are subjected to a catalytic esterification reaction to obtain an esterification reaction system. After the solvent is removed from the esterification reaction system, the oxygen-hybridized nonionic demulsifying material is obtained.

3. The preparation method according to claim 2, It is characterized in that The solvent in the solution of the fatty alcohol nonionic polyether in step (1) is an organic solvent; Preferably, the organic solvent comprises an aromatic organic solvent; Preferably, the aromatic hydrocarbon organic solvent includes any one of toluene, xylene, trimethylbenzene or ethylbenzene, or a combination of at least two thereof; Preferably, the fatty alcohol nonionic polyether is a linear type, and preferably the fatty alcohol nonionic polyether is formed by polymerization of ethylene oxide and propylene oxide with propylene glycol as an initiator; Preferably, the molar ratio of ethylene oxide to propylene oxide is 1 to 2:1; Preferably, the molecular weight of the fatty alcohol nonionic polyether is 3000 to 5000; Preferably, the molar ratio of the sum of propylene glycol, ethylene oxide and propylene oxide is 0.01 to 0.0125:1; Preferably, the ratio of the fatty alcohol polyether single dose to the organic solvent is 1-60 g:100 mL.

4. The preparation method according to claim 2 or 3, It is characterized in that The free radical initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide or dicumyl peroxide, or a combination of at least two thereof; Preferably, the free radical initiator accounts for 0.01 to 1 wt% of the mass of the fatty alcohol nonionic polyether; Preferably, the olefinic acid comprises an olefinic acid containing at least one carboxyl group and having 3 to 20 carbon atoms, preferably comprising any one or a combination of at least two of 2-butenoic acid, oleic acid, acrylic acid or undecenoic acid; Preferably, the olefinic acid accounts for 1 to 30 wt% of the mass of the fatty alcohol nonionic polyether; Preferably, the oil-soluble auxiliary agent includes any one of vinyltoluene, styrene, propylene or styrene, or a combination of at least two thereof; Preferably, the oil-soluble additive accounts for 0.1 to 10 wt % of the mass of the fatty alcohol nonionic polyether.

5. The preparation method according to any one of claims 2 to 4, It is characterized in that The polymerization reaction temperature is 60-100°C; Preferably, the polymerization reaction lasts for 2 to 8 hours.

6. The preparation method according to any one of claims 2 to 5, It is characterized in that The oxygen-rich organic acid in step (2) includes any one of lactic acid, citric acid or linoleic acid, or a combination of at least two thereof; Preferably, the oxygen-enriched organic acid accounts for 0.1 to 10 wt % of the mass of the fatty alcohol nonionic polyether.

7. The preparation method according to any one of claims 2 to 6, It is characterized in that The temperature of the catalytic esterification reaction is 80-150°C; Preferably, the duration of the catalytic esterification reaction is 2 to 8 hours.

8. The preparation method according to any one of claims 2 to 7, It is characterized in that The catalyst for catalyzing the esterification reaction is an organic catalyst; Preferably, the organic catalyst comprises a sulfonic acid and / or an organic acid salt; Preferably, the sulfonic acid comprises an aryl sulfonic acid, preferably any one or a combination of at least two of benzenesulfonic acid, p-toluenesulfonic acid, o-toluenesulfonic acid or m-toluenesulfonic acid; Preferably, the organic acid salt comprises an acetate, preferably any one or a combination of at least two of zinc acetate, cobalt acetate, acetic acid or ferric acetate; Preferably, the organic catalyst accounts for 0.01 to 1 wt % of the mass of the fatty alcohol nonionic polyether.

9. Use of the oxygen-hybrid nonionic demulsifying material according to claim 1 or the oxygen-hybrid nonionic demulsifying material prepared by the preparation method of the oxygen-hybrid nonionic demulsifying material according to any one of claims 2 to 8, It is characterized in that The oxygen-hybridized nonionic demulsifying material is used for demulsifying unconventional oil-water emulsions containing nano-micro solid particles.

10. The use according to claim 9, It is characterized in that The particle size of the nano-micro solid particles in the unconventional oil-water emulsion containing nano-micro solid particles is 20nm to 10μm; Preferably, the unconventional oil-water emulsion containing nano-micro solid particles is a water-in-oil emulsion; Preferably, the viscosity of the unconventional oil-water emulsion containing nano-micro solid particles is 50 mPa·s to 500 mPa·s; Preferably, the content of asphaltene in the unconventional oil-water emulsion containing nano-micro solid particles is 0.1wt% to 5wt%; Preferably, the water content of the unconventional oil-water emulsion containing nano-micro solid particles is 10 wt% to 75 wt%; Preferably, the content of nano-micro solid particles in the unconventional oil-water emulsion containing nano-micro solid particles is 0.1 wt% to 2 wt%; Preferably, the demulsification time is 30 min to 120 min; Preferably, the demulsification temperature is 40°C to 60°C; Preferably, the amount of oxygen-hybridized nonionic demulsifying material added in the demulsifier is 100 mg / L to 1200 mg / L.

Citation Information

Patent Citations

  • Demulsifying agent and preparation method and use thereof

    CN101352667A

  • Composite desalter and use method thereof

    CN101353591A

  • Reaction products of olefinically unsaturated carboxylic acids and polyetherols and their use as demulsifiers for crude oil emulsions

    US5661220A